Changing Paradigms in HR Management: or the impact of the COVID epidemic on the individual and the organisation – a theoretical overview - Gulya, Mátyás (Acta Carolus Robertus, 2024)
When reviewing the literature, one can find the basic idea that there is something good in every bad thing, i.e. “negative events can also have a positive effect”. I would like to examine this idea in the field of HR management, because the new behaviours and ways of working “learned” during the Covid period will live on in society after the pandemic is gone. Digitization processes were forced to accelerate in connection with the epidemic, making companies reconsider their production and service processes at the local level as well. A significant number of professional studies deal with the analysis of post-Covid social symptoms, mainly its impact on the economy and society. The appearance of the pandemic in 2020 immediately changed the daily operation of the economy and “reformed” the behaviour, attitude and future life of the actors. Society’s attitude has changed, and as a social response to this, preferences have changed in terms of shopping baskets, as well as attitudes to work and life. This paper examines the “necessary” paradigm shift of HR management from the perspective of adapting to the post-Covid symptoms of the 21st century. The question is whether the adaptation will succeed and whether the process can end with mutual benefits.